The Cape-Fear mercury : Friday, June 3rd 1775, no. 294 (LLMC-digital (Series), 1775)
Summary of a state convention held in Charlotte on May 19, 1775. Also includes brief articles on the Battle at Lexington with list of dead and wounded, and events in other colonies related to these matters.